THE IMPORTANCE OF FOREIGN LANGUAGE TEACHING IN THE PROFESSIONAL EDUCATION SYSTEM (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article explores the multifaceted benefits of incorporating foreign language education into professional curricula, the importance of foreign language teaching in the professional education system and the current state of foreign language teaching materials.